Displacement of mobile teeth produced by dental impression materials - Gómez Calvo, Abelardo A. ([editor no identificado], 1995)
Tesis (Master of Science in Dentistry)--University of Puerto Rico. Medical Sciences Campus School of Dentistry, 1995.